Postural sway serves as a predictive biomarker in balance and gait assessments for diabetic peripheral neuropathy screening: a community-based study - Yun-Ru Lai; Wen-Chan Chiu; Chi-Ping Ting; Yi-Fang Chiang; Ting-Yin Lin; Hui-Ching Chiang; Chih-Cheng Huang; Cheng-Hsien Lu (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Traditional screening methods for diabetic peripheral neuropathy (DPN) can be time-consuming in community settings. Balance and gait impairments are common in individuals with DPN, but these functional impairments are often not detectable with standard neurological examinations. This study aimed to examine whether quantitative balance and gait assessment could serve as a viable alternative screening tool for DPN. Methods All participants were recruited from a community-based daycare center and underwent peripheral nerve function assessments, including the Toronto Clinical Neuropathy Score (TCNS), sural nerve conduction studies (amplitude and velocity) for large fiber function, and Sudoscan testing for small fiber function. Subsequently, participants underwent balance and gait assessments, including static postural sway measurements and gait analysis of spatiotemporal parameters and joint range of motion (ROM) assessment during walking. Results Of the 146 participants, 35 had diabetes, including 22 with DPN, while 111 were healthy controls. Participants with DPN demonstrate increased postural sway velocity and total path length, along with reduced gait speed, shorter stride length, and decreased range of motion in hip flexion and extension. The logistic regression analysis identified diabetes duration and postural sway velocity as the only significant predictors of DPN presence. Postural sway velocity demonstrated strong correlations with elevated TCNS, reduced sural sensory nerve action potential and sensory nerve conduction velocity, and lower Sudoscan values in hands and feet. Additionally, receiver operating characteristic analysis yielded a sensitivity of 68.2%, specificity of 85.5%, and an area under the curve of 0.76, with a cut-off value of 0.98 cm/s. Conclusions Balance and gait impairments are prevalent among participants with DPN. This study supports the integration of balance and gait assessments into community-based screening protocols to facilitate early identification and intervention. Postural sway velocity emerged as a practical early biomarker for the screening of DPN.